Financial Restructuring and its Impact on Shareholders’ Wealth in Selected Companies in India - Joshi, Nisarg A. (Indian Journal of Finance, 2022)
Purpose : The purpose of the study was to analyze the effect of financial restructuring on shareholders’ wealth of manufacturing companies. This study investigated if there was a significant difference in shareholders’ wealth of the firms after the restructuring. Methodology : This study included a sample of 146 firms of different manufacturing sectors and related sub-sectors in India that had undergone financial restructuring. This study involved a two-stage methodology. In the first part, paired sample t-test was used to investigate the significant difference in financial ratios in pre and post-restructuring periods. In the second part of the methodology, the focus was given to checking the impact of restructuring on the shareholders’ wealth of the companies in the post-restructuring period using various techniques like factor analysis, correlation matrix, and multiple regression analysis. Findings : The results showed a significant difference in four financial parameters in the pre-and post-restructuring periods. Moreover, it was also found that restructuring considerably impacted the shareholders’ wealth of firms in all factors except growth. Practical Implications : These results are recommended to financial institutions, banks, and executives. This study may also be used for understanding the reasons behind restructuring and to evaluate whether restructuring created value for shareholders or not. This study could be used to analyze the shift in the structure after restructuring. Originality/Value : The study found that restructuring improved the shareholders’ wealth of the firms in the short-term and long-term.